Physical and physicochemical properties of binary and multicomponent semiconductors of CuBr-CuI system - I. A. Kirovskaya; T. L. Bukashkina; E. P. Surovoy; A. V. Yureva; V. E. Surovaya; L. V. Kolesnikov; V. B. Goncharov; O. V. Kropotin (Омский научный вестник)
Solid solutions of the CuBr-CuI system of various composition have been obtained, certified according to X-ray and thermographic studies as substitution solid solution with cubic structure of sphalerite. Microscopic, magnetic studies of the obtained solid solutions and binary components of the system have also been conducted. The specific electrical conductivity, forbidden bandwidth, Fermi level position relative to the valence band top and the magnetic susceptibility have been identified. Predominance of diamagnetism in the studied components has been shown. Both linear and extreme changes in the studied properties with changes in composition have been noted. Preliminary considerations have been made about the potential for use the solid solutions of extreme composition in sensor technology.